ANALISA PENGARUH WAJIB PAJAK DALAM MEMBAYAR PAJAK KENDARAAN BERMOTOR - Intan Nio Kusumawati; Arif Nugroho Rachman (FEB Universitas Sultan Ageng Tirtayasa, 2021)
The income earned by a country with one of the largest receipts comes from taxes. Taxation as one of the main factors in increasing state revenues so the observance of waib tax must be increased. This study aims to analyze the influence of taxpayer awareness, socialization of taxation, untabilitas pelayaan public and income level in the observance of taxpayers. This research is in order to obtain information and data related to the problem that will be the research material using primary data, namely through the dissemination questionnaire of 100 samples using purposive sampling sample determination method. Data analysis method using multiple linear regression. This study has results on taxpayer awareness, socialization of taxation and income level partially affect taxpayer compliance and accountability of public services partially does not affect taxpayer compliance in SAMSAT Karanganyar Regency. The results of simultaneous research on taxpayer awareness, taxation sociality, public service accountability and income level have a positive influence on taxpayer compliance in SAMSAT Karanganyar Regency.